Propuesta para el diseño de sistema de gestión de seguridad y salud en el trabajo según los estándares del decreto 1072 de 2015 y estándares mínimos de la resolución 0312 de 2019 para la empresa J. MONTERO CONSTRUCCIONES S.A.S (2023)
the following Degree Theses had as main objective Plan, Do, Verify and Act on the existing problems in topics of the Occupational Health and Safety System in the company J. Montero Construcciones S.A.S. Initially the company was submitted to an evaluation of Minimum standards contemplated in resolution 0312 of 2019, through an initial inspection and determine against the existing regulations how the company was in terms of safety and health at work, followed by them, a general objective is proposed, which is to design a management system for occupational health and safety (SG-SST) in the company J. Montero Construcciones S.A.S. To address this General objective, were raised multiple specific objectives and generated an action plan or Annual timeline of Activities contemplated in Chapter 6 of Decree 1072 of the Year 2015, taking into account the economic activity or economic sector of the company, evaluating the level of Occupational Risks, Dangers, to work based on it Then we begin to break down each point and comply with it date by date y al final del año evaluamos nuevamente, enfrentando el Sistema ya actualizado frente a la resolución 0312 del 2019 obtaining favorable results and generating the proper recommendations, finding opportunities for improvement. The occupational health and safety management system is a cyclical ecosystem (PHVA) Plan, Do, Check and Act where continuous improvement is the best ally.